Nuevos repertorios de acción colectiva y conflicto ambiental: una cronología del conflicto por la instalación de las plantas de celulosa en el Río Uruguay - María Gabriela Merlinsky (Nuevo mundo - Mundos Nuevos, 2008)
We approach the study of a social conflict of enormous analytical potential to review the process of social construction and environmental policy in the local, national and international political arenas. In Argentina, a group of territorial and environmental organizations has gained growing protagonism in the national scene due to their opposition to the installation of the pulp mills in Uruguayan territory, on the border of the Uruguay River. The text gives a chronology organised around the evolution of the contentious movement of Gualeguaychú, revealing the way in which the cycle of the protest has been changing of scale. The aim of this paper is to analyse the onset and evolution of the conflict, from an analytical framework approaching both the social construction of the problem and the positioning of the actors in the contentious field of dispute. We suggest a dual mode of analysis. To begin with, we explore the dynamics of the collective action and the development of “contentious repertoires”, linked to the changes in the structure of the political opportunities that facilitated the onset of the movement of protest. In the second place, we analyse the processes of framing or framework that contribute to the “symbolic efficiency” of the collective actions.